Analisis Loyalitas Pelanggan Pada Skincare Wardah Dikota Bima - Nabila Putri Sakinah; Ismunandar Ismunandar (JUEB : Jurnal Ekonomi dan Bisnis, 2022)
Satisfying consumer needs is the dream of every company. Apart from being an important factor for the survival of the company, meeting consumer needs can increase its superiority in the competition. Consumers who are satisfied with the quality and price of the product tend to repurchase the product and reuse the product when the same need reappears in the future. This study aims to determine the analysis of customer loyalty on skincare wardah in the city of Bima. This research uses a quantitative approach with a survey method, while this type of research includes descriptive research. The population in this study were customers who used Wardah skincare, the number of samples taken in this study were 96 respondents. The sample used in this study was accidental. The research instrument used a questionnaire with a Likert scale. Data analysis used validity test, reliability test, and on sample test. To test the independent variables using SPSS (Statistical Service Product Solutions) version 23.00. Research results Based on the results of the one sample t-test at Skincare Wardah City of Bima it is said to be good because it is more than 70%, which means that Customer Loyalty to Skincare Wardah City of Bima is in accordance with consumer desires.